Feasibility and accuracy of fusion imaging during thoracic endovascular aortic repair - Schulz, Christof; Schmitt, Matthias; Böckler, Dittmar; Geisbüsch, Philipp (Journal of vascular surgery, 2016)
To evaluate accuracy and feasibility of fusion imaging during thoracic endovascular aortic repair (TEVAR).
Available online 10 November 2015
Gesehen am 26.05.2020